2023
DOI: 10.1038/s42003-023-04805-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide cross-trait analysis and Mendelian randomization reveal a shared genetic etiology and causality between COVID-19 and venous thromboembolism

Abstract: Venous thromboembolism occurs in up to one-third of patients with COVID-19. Venous thromboembolism and COVID-19 may share a common genetic architecture, which has not been clarified. To fill this gap, we leverage summary-level genetic data from the latest COVID‐19 host genetics consortium and UK Biobank and examine the shared genetic etiology and causal relationship between COVID-19 and venous thromboembolism. The cross-trait and co-localization analyses identify 2, 3, and 4 shared loci between venous thromboe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A 'leave one out' analysis was conducted to assess the in uence of individual SNPs on the exposure-outcome relationship, with a p-value over 0.05 signifying no horizontal pleiotropy [29] . To clarify whether the immune cell traits and RA genetically share the same genetic variant, we performed gene colocalization analysis [30] . To mitigate false positives in multiple testing, false discovery rate (FDR) correction was applied.…”
Section: Discussionmentioning
confidence: 99%
“…A 'leave one out' analysis was conducted to assess the in uence of individual SNPs on the exposure-outcome relationship, with a p-value over 0.05 signifying no horizontal pleiotropy [29] . To clarify whether the immune cell traits and RA genetically share the same genetic variant, we performed gene colocalization analysis [30] . To mitigate false positives in multiple testing, false discovery rate (FDR) correction was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, immunothrombosis plays a central pathogenic role in sCOVID-19 connecting it to respiratory failure and systemic hypercoagulability. Prior cross-trait meta- and colocalization analyses indicated that certain known VTE-associated genes (e.g., ABO, FUT2 , and ADAMST13 , et al) were strongly associated with COVID-19 diseases severity ( 19 , 20 ). An MR investigation involving 12 coagulation factors and COVID-19 severity reported that VWF is strongly correlated with COVID-19 susceptibility and hospitalization ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…An MR investigation involving 12 coagulation factors and COVID-19 severity reported that VWF is strongly correlated with COVID-19 susceptibility and hospitalization ( 19 ). Huang and colleagues performed an MR analysis to genetically predict that VTE is intricately linked to enhanced COVID-19 infection and hospitalization risks ( 20 ). This report further validated the direct correlation between genetically estimated VTE and enhanced sCOVID-19 with respiratory failure risk.…”
Section: Discussionmentioning
confidence: 99%